Creating visual effects in Maya : fire, water, debris, and destruction - Lanier, Lee, 1966- (Focal Press, 2014)
"Produce mind-blowing visual effects with Autodesk Maya. Gain the practical skills and knowledge you need to recreate phenomenon critical to visual effects work, including fire, water, smoke, explosions, and destruction, as well as their integration with real-world film and video. In Creating Visual Effects with Maya, Maya-master Lee Lanier has combined the latest studio techniques with multi-chapter, hands-on projects and professionally vetted workflows to bolster your CG toolkit. Engaging, full-color tutorials cover: - Creating foliage, fire, and smoke with Paint Effects - Growing Maya Fur and nHair on clothing, characters, and sets - Replicating water, smoke, sparks, swarms, bubbles, and debris with nParticles and nCloth - Controlling scenes and simulations with expressions and MEL, Python, and PyMEL scripting - Adding dust, fog, smoke, rippling water, and fireballs with Fluid Effects containers - Creating damage with Effects presets, deformers, and animated textures - Matchmoving and motion tracking with Maya and MatchMover - Creating complex destruction by combining rigid bodies, nParticles, nCloth, and Fluid Effects - Setting up, rendering, and compositing mental ray render passes with Autodesk Composite, Adobe After Effects, and The Foundry Nuke"--